Comparison of melamine determination as reference value in food simulant by gravimetric method and high performance liquid chromatography - Lapviboonsuk, Jutathip; Tagheen, Pochaman; Lapviboonsuk, Sompop (Bulletin of Applied Sciences, 2022)
This study aimed to compare the approaches used for assigning reference values for proficiency testing scheme in food simulant (acetic acid, 3% (w/v)) using gravimetric technique and high performance liquid chromatography (HPLC) as according to DD CEN/TS 1313027: 2005. The PT samples used in this study were required to investigate for homogeneity and stability. These samples were examined and met the standard requirements (ISO 13528: 2005). The determinations of melamine content were performed by using HPLC and gravimetric method. From the experiment results, the amounts of melamine in food simulant were 5.04 and 5.00 mg/kg, respectively. Moreover, the uncertainties of measurement were also estimated and found that the expanded uncertainties at 95% confidence interval were 0.30 and 0.06 mg/kg, respectively. The comparison between the reference values of HPLC and gravimetric method was performed by using En value. The En value showed non-significant difference for both determination methods of melamine values.